“I am a Unique Student”: Differentiate Instructions Applied in English Classroom in Eastern Taiwan - Sari, Dwi Rosita; Suwandi, Edi (English Department, Universitas Negeri Surabaya, 2024)
Student’s diversity and uniqueness should not be the reason for left-behind student in the learning process. Process, content, and product are the main elements of differentiated instruction that bridge the diversity issues in the classroom, including in the process of learning English as a foreign language in Taiwan. Differentiate instruction is believed as the fittest approach that can reach every single student’s profile, uniqueness, readiness, and schemata understanding which is understood as the element of reaching success in the English teaching and learning process. The approach then enhances students’ self-confidence and manages the structural thinking ideas through the variety of activities conducted during the class. The research method was used qualitatively involving English class observation of 22 students which was performed at one of the Junior High Schools in Eastern Taiwan. The research results provided wider information by preparing various media and activities, recognizing students’ competency levels, and activating students’ awareness of the teacher’s instructions.